Dithering‐based real‐time control of cascaded silicon photonic devices by means of non‐invasive detectors. Issue 2 (22nd March 2021) - Zanetto, Francesco; Grimaldi, Vittorio; Toso, Fabio; Guglielmi, Emanuele; Milanizadeh, Maziyar; Aguiar, Douglas; Moralis‐Pegios, Miltiadis; Pitris, Stelios; Alexoudi, Theoni; Morichetti, Francesco; Melloni, Andrea; Ferrari, Giorgio; et al.
Abstract: Real‐time control of multiple cascaded devices is a key requirement for the development of complex silicon photonic circuits performing new sophisticated optical functionalities. This article describes how the dithering technique can be leveraged in combination with non‐invasive light probes to independently control the working point of many photonic components. The standard technique is extended by introducing the concept of orthogonal dithering signals to simultaneously discriminate the effect of different actuators, while the idea of frequency re‐use is discussed to limit the complexity of control systems in cascaded architectures. After a careful analysis of the problem, the article presents an automated feedback strategy to tune and lock photonic devices in the maxima/minima of their transfer functions with given response speed and sensitivity. The trade‐offs of this approach are discussed in detail to provide guidelines for the design of the feedback loop. Experimental demonstrations on a mesh of Mach‐Zehnder interferometers and on cascaded ring resonators are discussed to validate the proposed control architecture in different scenarios and applications.